Mandatory joint audit and audit quality in the context of the European blue chips - Garcia-Blandon, Josep; Castillo-Merino, David; Argilés-Bosch, Josep M.; Ravenda, Diego (Journal of Business Economics and Management, 2021)
This study investigates audit quality under joint and single audit regimes with a sample of large European firms. Both, the economic relevance of these companies, and the fact that the impact of joint audit on audit quality should be stronger when the audited company is a blue-chip firm motivate the study. If mandatory joint audit were positively associated with audit quality, French firms, under mandatory joint audit since 1966, should present higher audit quality compared to their European peers. The results do not indicate this to be the case. Specifically, similar levels of discretionary accruals are observed for French and other European firms. Furthermore, for the first time in the literature, evidence is reported indicating that French firms may even present lower audit quality than their European peers, when audit quality is measured by the likelihood of just beating earnings benchmarks. These results are expected to inform the ongoing debate in several countries about joint audits.